Implementasi Sistem Absensi Pada PG-TK AISYIYAH VI Sebagai Pendataan Absen Guru - Gadafi Gadafi; Sumarno Sumarno; Cindy Taurusta (SMATIKA JURNAL : STIKI Informatika Jurnal, 2024)
PG-TK AISYIYAH is a school with limited information system facilities, so an information system was created that refers to the method of recording attendance using a website with the aim of facilitating a more efficient and practical process when taking attendance. The purpose of this study is to design an attendance system that is applied to the website and automatically the attendance data will be listed, containing the name, time, minutes. In addition, an analysis was carried out at the school and data collection was carried out on teacher personal data. The research method used is through the stages of data analysis, design of the attendance system, implementation of the attendance system, testing and maintenance. At the testing stage using blackbox testing. The results of the study are that the attendance system shows that the application runs smoothly without errors. The admin confirms the attendance data and minutes provided by the teacher. All related entities in the application, with data from the teacher directly entering the admin system for confirmation.